Determination of Radiogenic 87Sr/86Sr and Stable δ88/86SrSRM987 Isotope Values of Thirteen Mineral, Vegetal and Animal Reference Materials by DS‐TIMS. Issue 2 (3rd February 2020) - Brazier, Jean‐Michel; Schmitt, Anne‐Désirée; Pelt, Eric; Lemarchand, Damien; Gangloff, Sophie; Tacail, Théo; Balter, Vincent
Abstract : This work presents new 87 Sr/ 86 Sr and δ 88/86 SrSRM987 isotopic values of thirteen mineral, vegetal and animal reference materials. Except for UB‐N, all our results are consistent with previously published data. Our results highlight intermediate precisions among the best presently published and a non‐significant systematic shift with the calculated δ 88/86 SrSRM987 mean values for the three most analysed reference materials in the literature (i.e., IAPSO, BCR‐2 and JCp‐1). By comparison with the literature and between two distinct digestions, a significant bias of δ 88/86 SrSRM987 values was highlighted for two reference materials (UB‐N and GS‐N). It has also been shown that digestion protocols (nitric and multi‐acid) have a moderate impact on the δ 88/86 SrSRM987 isotopic values for the Jls‐1 reference materials suggesting that a nitric acid digestion of carbonate can be used without significant bias from partial digestion of non‐carbonate impurities. Different δ 88/86 SrSRM987 values were measured after two independent Sr/matrix separations, according to the same protocol, for a fat‐rich organic reference material (BCR‐380R) and have been related to a potential post‐digestion heterogeneity. Finally, the δ 88/86 SrSRM987 value differences measured between animal‐vegetal and between coral‐seawater reference materials agree with the previously published results, highlighting an Sr isotopic fractionation along the trophic chain and during carbonate precipitation. Abstract : Key Points: New 87 Sr/ 86 Sr and δ 88/86 SrSRM987 isotopic values of thirteen mineral, vegetal and animal reference materials are presented. Biases δ 88/86 SrSRM987 isotopic values generated by digestion procedure and Sr/matrix separation were investigated. Our results are in agreement with previous work highlighting a Sr isotopic fractionation along the trophic chain.